Maternal imaginary and criminality: Subjectivities extracted from the narratives of the digital journalistic press (Research, Society and Development, 2024)
Human subjectivity consists of experiences, symbolic and emotional elements, imaginations and drives. Exemplified by intergenerational inheritances that transmit idealizations and fantasies. Society binds women to motherhood, but the desire to be a mother is subjective, as motherhood involves a set of essential principles for the child's development. The maternal imaginary - a phenomenon full of enchantment - and the impact of the reverberations between work, motherhood and stress in contemporary life lead to the emergence of destructive behavior, revealed by the marks of criminality; the premise of the "good mother" is transmuted into the "homicidal mother". The aim is to analyze the maternal subjectivities revealed in the crime of homicide against offspring, in order to understand homicidal mothers. This qualitative exploratory - descriptive and cross-sectional study used scientific articles, psychoanalytical works and cases of maternal homicide against offspring, with concealment of the corpse, published in the digital press between 2020 and 2022. The conclusion is that maternal subjectivity changes due to factors that affect motherhood, such as the impact of intergenerational inheritance, multiple illnesses, loss of personal identity, egocentrism and narcissism, making it essential for social representatives - politicians, health professionals and other professionals - to look at these phenomena.